A method for analyzing turbulence models - Grebene, V. N. (2001)
In this article we introduce a concept based on the differential constraints method to examine the closure procedure in Turbulence Models. We show how this concept may be applied to study the problem of interaction and mixing between two semi-infinite homogeneous turbulent flow fields of different scales.